Colony-Level Efficacy of Mentha piperita, Thymus vulgaris and Eucalyptus globulus Essential Oil Nanoemulsions Against Varroa destructor - Gunesdogdu, Mustafa (Springer, 2026)
Honey bees (Apis mellifera L.) are essential for ecosystem stability and agricultural production; however, one of the most destructive threats to colonies is the mite Varroa destructor. Although conventional chemical acaricides can provide short-term control, resistance development and residue concerns remain major challenges. Plant-derived essential oils have therefore attracted attention as alternative control agents. In this study, the field efficacy of nanoemulsions (NEms) prepared from peppermint (Mentha piperita; P-NEms), thyme (Thymus vulgaris; T-NEms), and eucalyptus (Eucalyptus globulus; E-NEms) oils against Varroa mites was evaluated at three doses (50, 100, and 200 ppm), and compared with a positive control (amitraz) and a negative control (no treatment). All tested nanoemulsion formulations significantly reduced Varroa mite density, with the highest efficacy (percentage reduction relative to initial mite counts) observed at the 200 ppm dose. The T-NEms200 treatment exhibited the strongest acaricidal activity (75.3%). Peppermint and eucalyptus NEms also achieved high efficacy. The positive control, amitraz, showed 53.5% efficacy and was less effective than the higher NEms doses, while mite loads increased in untreated colonies. The nanoscale droplet structure of the formulations may have contributed to enhanced contact between active compounds and mites. Overall, these findings demonstrate that essential oil-based nanoemulsions reduced Varroa mite populations in a concentration-dependent manner at the colony level. However, the present study focused on efficacy, and further research is required to evaluate potential effects on bee health, brood development, and residue levels in hive products before practical recommendations can be made.
Keywords: Apis Mellifera; Natural Acaricide; Pesticide Formulation; Nanotechnology; Varroa Mortality